Profil Anak Jalanan di Daerah Bekas Lokalisasi Balong Cangkring Mojokerto - Muhammad Gunawan Sadjali; A. Rosyid Al Atok; Siti Awaliyah (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2021)
The most dominant factor causing street children is due to family economic problems that are not able to meet the necessities of life. Apart from economic factors, the family can also be relied on by cultural, social, and parental education factors that are still low so that they cannot motivate children to live better lives. The income that street children earn varies depending on the time on the road and the type of work they choose. The average income of street children is around Rp. 50,000, - up to Rp. 100.000, - with a choice of professions as buskers, hawkers, and car glass cleaners. The spots for street children are mostly found, which are blocked by red lights or other places such as the center of the situation. The behavior of active and passive assisted members is no different, but when compared to passive members, it is very easy for active members and is directed to a better pattern of behavior. The purpose of this research is to look at the background of street children in Balong Cangkring which is focused on the reasons for being street children; income; a gathering place; and the behavior of active and passive assisted members. This research uses qualitative research with a case study approach, descriptive analysis techniques, semi-structured interviews and semi-participant observation. Participants were taken by using purposive sampling technique as many as 8 respondents.